Oligosaccharide Content and in vitro Protein Digestibility of Twenty Commercial Soy-Based Powder Drinks in Indonesia - Faridah, D.N.; Andarwulan, N.; Purnomo, E.P.; Saifatah, L.; Kurniawan, S.K. (Asian Journal of Chemistry, 2014)
This study aims to analyze the oligosaccharide content and in vitro protein digestibility in twenty commercial soy-based powder drinks. Twenty commercial products were sampled and grouped by consumer ages; 0-1 year, 1-3 years and older than 3 years old (ordinary and special consumers). The oligosaccharides were analyzed by means of HPLC. The result showed stachyose and raffinose were found in the soy-based powder drink of grouped age of older than 3 years old, but were not detected in those for 1-3 years old and 0-1 year old consumers. The lowest in vitro protein digestibility were found in the samples for grouped age of more than 3 years old consumer. Samples which are enriched with dairy protein had lower protein content, but their protein digestibility and protein solubility were higher than those of samples which were added with soybean as protein source.